(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
State-indicating words, encompassing stative verbs, adjectives, copular constructions, and nominal predicates, express static situations, properties, or states rather than dynamic actions. This article explores the semantic and structural differences in expressing states between Uzbek (a Turkic, agglutinative language) and English (an Indo-European, analytic language), with a focus on translation challenges. In English, states are primarily conveyed through stative verbs (e.g., know, be, have) and linking verbs with adjectives, while Uzbek often employs zero copula in the present tense, particle or verbal copulas depending on tense/aspect, and postpositional constructions. Key challenges include aspectual mismatches, copula omission/insertion, lexical gaps (lacunae), and degrees of stativity. Drawing on contrastive linguistics and examples from literary translations, the study highlights system asymmetries that lead to non-equivalence in translation. Recommendations for translators emphasize contextual adaptation and functional equivalence to preserve semantic nuance.